Anti–Interleukin-10 Unleashes Transcriptional Response to Leishmanial Antigens in Visceral Leishmaniasis Patients. (2nd July 2020) - Singh, Om Prakash; Syn, Genevieve; Nylén, Susanne; Engwerda, Christian; Sacks, David; Wilson, Mary E; Kumar, Rajiv; Chakravarty, Jaya; Sundar, Shyam; Blackwell, Jenefer M; Fakiola, Michaela
Abstract: Visceral leishmaniasis (VL; Leishmania donovani ) cases produce interferon-γ and tumor necrosis factor in response to soluble leishmanial antigen (SLA) in whole-blood assays. Using transcriptional profiling, we demonstrate the impact of interleukin-10 (IL-10), a cytokine implicated in VL, on this response. SLA stimulation identified 28 differentially expressed genes (DEGs), 17/28 in a single network with TNF as hub. SLA plus anti–IL-10 produced 454 DEGs, 292 in a single network with TNF, IFNG, NFKBIA, IL6, and IL1B as hubs in concert with a remarkable chemokine/cytokine storm. Our data demonstrate the singular effect of IL-10 as a potent immune modulator in VL.